Apurinic/Apyrimidinic Endonuclease 1 and Tyrosyl-DNA Phosphodiesterase 1 Prevent Suicidal Covalent DNA-Protein Crosslink at Apurinic/Apyrimidinic Site - Lebedeva, Natalia A.; Rechkunova, Nadejda I.; Endutkin, Anton V.; Lavrik, Olga I. (Frontiers in Cell and Developmental Biology, 2021)
Bifunctional 8-oxoguanine-DNA glycosylase (OGG1), a crucial DNA-repair enzyme, removes from DNA 8-oxo-7,8-dihydroguanine (8-oxoG) with following cleavage of the arising apurinic/apyrimidinic (AP) site. The major enzyme in eukaryotic cells that catalyzes the cleavage of AP sites is AP endonuclease 1 (APE1). Alternatively, AP sites can be cleaved by tyrosyl-DNA phosphodiesterase 1 (TDP1) to initiate APE1-independent repair, thus expanding the ability of the base excision repair (BER) process. Poly(ADP-ribose) polymerase 1 (PARP1) is a regulatory protein of DNA repair. PARP2 is also activated in response to DNA damage and can be regarded as the BER participant. Here we analyze PARP1 and PARP2 interactions with DNA intermediates of the initial stages of the BER process (8-oxoG and AP-site containing DNA) and their interplay with the proteins recognizing and processing these DNA structures focusing on OGG1. OGG1 as well as PARP1 and PARP2 form covalent complex with AP site-containing DNA without borohydride reduction. AP site incision by APE1 or TDP1 removal of protein adducts but not proteins’ PARylation prevent DNA-protein crosslinks.